527 Multicentric Evaluation of Stereotactic Radiosurgery for Koos Grade IV Vestibular Schwannoma in Young Patients. (April 2023) - Dumot, Chloe; Pikis, Stylianos; Mantziaris, Georgios; Xu, Zhiyuan; Lunsford, L. Dade; Sheehan, Jason P.
Abstract : INTRODUCTION: Koos IV vestibular schwannoma (VS) are preferably treated by surgery. However, SRS can be an alternative for patients with contraindications or who refuse surgery. SRS for Koos IV patient younger than 45 years old has not been previously studied and could be associated with more complications. METHODS: This is a retrospective multicentric study, performed under the International Radiosurgery Research Foundation. Patients 45 years old, treated primarily for a Koos IV VS with single-session SRS, presenting with non life-threatening or incapacitating symptoms, with a follow-up ≥1 years were included. RESULTS: 176 patients with a median age of 36 years (IQR 9) and a median tumor volume of 9.3 cm 3 (IQR 4.7) were included. Before SRS, serviceable hearing, facial nerve weakness (House-Brachman >1) and trigeminal neuropathy was present in 51.7%, 8.5%, and 34.1% respectively. The median prescription dose was 12Gy (IQR 0.5). At a median follow-up of 3.1 years (IQR 4.5), tumor stability and regression were 38.9% and 54.3%, respectively. The 5- and 10-year progression-free rate was 90.9% and 86.7%. Early tumor enlargement occurred in 10.9% of cases. The probability of serviceable hearing preservation at 5- and 10-years was 56.8% and 45.2%, respectively. The probability of improvement or preservation of facial nerve function was 95.7% at 5 and 10-years. Adverse radiation effects were noted in 19.9%, 6 of them where managed with surgical resection of the VS. New-onset hydrocephalus occurred in 4.0%. CONCLUSIONS: Single-session SRS in selected Koos IV VS can be an alternative to surgery in a selected group of patients 45 years old. Long-term follow-up is warranted.